2003
DOI: 10.1034/j.1399-5618.2003.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Right prefrontal TMS versus sham treatment of mania: a controlled study

Abstract: It is possible that the previous results were due to an effect of left TMS to worsen mania. Alternatively, it is noted that the present patient group had much more psychosis than the previous study of TMS in mania, and depression studies have reported that psychosis is a poor prognostic sign for TMS response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 10 publications
1
41
0
3
Order By: Relevance
“…A possible alternative to ECT as a physical treatment, repetitive transcranial magnetic stimulation (rTMS) has not been shown to have unequivocal antimanic efficacy in a single blind study against sham-rTMS ( Kaptsan et al 2003) (CE ''E'').…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…A possible alternative to ECT as a physical treatment, repetitive transcranial magnetic stimulation (rTMS) has not been shown to have unequivocal antimanic efficacy in a single blind study against sham-rTMS ( Kaptsan et al 2003) (CE ''E'').…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…0.01) for patients treated with right, rather than left prefrontal TMS at 20 Hz. Although an open-label study using right high-frequency prefrontal TMS in the treatment of bipolar mania found that TMS was associated with a reduction in manic symptoms [55] , Kaptsan et al [56] could not replicate its result in a sham-controlled study.…”
Section: Tms In Maniamentioning
confidence: 97%
“…Response to right prefrontal rTMS was superior, with a 71% decline in mean YMRS scores, compared to left prefrontal rTMS (29% change). However, a sham-controlled, follow-up study by the same group in 25 manic patients found no difference between active and sham treatment, despite using the same treatment approach (Kaptsan et al 2003). In both studies, most patients were on concurrent medications (lithium, anticonvulsants, and/or antipsychotic medications).…”
Section: Rtms In the Treatment Of Acute Maniamentioning
confidence: 96%